Analysis of the Kiosk Rental Pricing System in Increasing Revenue at the Regional Public Company of Ya’ahowu Market Gunungsitoli–Nias - Mendrofa, Dista Wati; Bate'e, Maria Magdalena; Mendrofa, Martha Surya Dinata; Telaumbanua, Eliagus (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
This study aims to analyze the kiosk rental pricing system as an effort to increase the revenue of the Regional Public Company (Perumda) Pasar Ya’ahowu Gunungsitoli – Nias, as well as to identify the influencing factors. The background of this research is based on the increasing number of vacant kiosks, indicating a low level of tenant interest, which is suspected to be caused by a suboptimal pricing system, including factors such as location and purchasing power. The research method used is descriptive qualitative, with data collection techniques through observation, in-depth interviews, and documentation. Research informants consisted of market management and kiosk tenants. The results of the study indicate that the pricing system remains administrative in nature and has not fully considered market aspects such as consumer segmentation, competitive conditions, and purchasing power. Internal factors such as operational costs and company revenue targets influence pricing policies, while external factors include kiosk location, local economic conditions, and competing businesses. The pricing strategy applied has not fully adapted to market dynamics, and although price evaluations are conducted periodically, they have not been responsive to changes in demand and kiosk conditions. The findings suggest that a fair, flexible, and market-oriented pricing system is necessary to increase kiosk occupancy and sustainably boost company revenue.